The Scream: Benign Thyroid Tissue as a Lateral Neck Mass. Issue 3 (May 2022) - Wiles, Austin; Sayeed, Sadia
Abstract: Variant anatomy and cytomorphological overlap between benign and malignant conditions can coincide to produce diagnostic error. We report the case of an unusually shaped thyroid gland bearing a follicular adenoma interpreted as a metastatic papillary thyroid carcinoma. The shape of the gland had a striking resemblance to The Scream, a painting by Edvard Munch, and directly contributed to the misdiagnosis. We discuss the known embryological mechanisms of thyroid development, ultrasound radiological characteristics of thyroid examination, and the cytomorphologic interpretation of thyroid tissue. The constellation of these elements and the resultant error is eloquently illustrated by Munch's artistic inspiration.